The influence of professional development program on the leadership style ofschool principals (linemanagers) in Abu Dhabi governmental schools - Tuffaha, Mohand (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the practices of professional development program in improving leadership style of school principals (line managers) in Abu Dhabi governmental school, UAE. Qualitative research design with Case-study approach was selected to offer in depth analyzing and evaluating results obtained from anstandardized survey. A questionnaire made up of eight Likert questionnaires and three open- ended questions has been administrated. The Survey has been designed based on Ministry of Education School Inspection Framework in UAE. The main goal of the aforementioned framework is to explore the relationship between two variables, professional development program, and leadership style of school principals. This study has been carried out in eight randomly selected public secondary schools located in Abu Dhabi – Al Ain. The target population was each of the principles running the eight schools. The results showed that, as a consequence of professional development program, all principals had acquired new strategies to improve their skills in some spots, but uncertainty appeared in the rest knowledge, strategies and skills. Finally, a bundle of gradual and planned training strategies matching with the requirements of school principals to face internal and external challenges are recommended to improve leadership style of school principals in Abu Dhabi.